2020
DOI: 10.1097/brs.0000000000003765
|View full text |Cite
|
Sign up to set email alerts
|

Semitendinosus Tendon Augmentation for Prevention of Proximal Junctional Failure

Abstract: Study Design. Retrospective cohort study. Objective. The aim of this study was to compare the incidence of proximal junctional kyphosis (PJK), proximal junctional failure (PJF), and clinical outcomes of patients who did and did not receive posterior ligament complex (PLC) augmentation using a semitendinosus allograft when undergoing long-segment posterior spinal fusion for adult spinal deformity. Summary of Background D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…For each study, PJK incidence, Revision Rate for PJK (RR), PJF incidence, reported clinical outcomes and complications were reported in Table 3. Twelve of the included studies reported on PJK incidence, 28-31,33-36,38,39,41,43 10 on revision rate for PJK, 28-31,33,35,36,38,39,41 13 on PJF incidence, 29,32,34-40,42-45 5 on any clinical outcome measure 28,38,40,41,45 and 10 on complications. 28-30,35-39,41,45 Four studies 28-30,37,45 did not elaborate on the type of complications, and could thus not be converted to the classification of Glassman et al 27 If reported, the clinical outcome measures were further elucidated in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For each study, PJK incidence, Revision Rate for PJK (RR), PJF incidence, reported clinical outcomes and complications were reported in Table 3. Twelve of the included studies reported on PJK incidence, 28-31,33-36,38,39,41,43 10 on revision rate for PJK, 28-31,33,35,36,38,39,41 13 on PJF incidence, 29,32,34-40,42-45 5 on any clinical outcome measure 28,38,40,41,45 and 10 on complications. 28-30,35-39,41,45 Four studies 28-30,37,45 did not elaborate on the type of complications, and could thus not be converted to the classification of Glassman et al 27 If reported, the clinical outcome measures were further elucidated in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 4 were prospective- and 14 were retrospective cohort studies. The studies that were included reported on tether fixation, 28 - 34 prophylactic 2-level vertebroplasty (2-PVP), 32 , 35 - 40 transverse process hooks (TPH), 32 , 41 , 42 flexible rods (FR), 43 multilevel stabilization screw (MLSS), 44 and sublaminar tapes (ST). 45 These surgical techniques are schematically illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations